Very fast electrophoretic separation on commercial instruments using a combination of two capillaries with different internal diameters - Tůma, Petr; Opekar, František; Samcová, Eva (Electrophoresis, 2013)
A capillary formed by connecting a 9.7 cm-long separation capillary with id 25 μm with an auxiliary 22.9 cm-long capillary with id 100 μm (coupled capillary) was tested for electrophoretic separation at high electric field intensities. The coupled capillary was placed in the cassette of a standard electrophoresis apparatus. It was used in the short-end injection mode for separation of a mixture of dopamine, noradrenaline, and adrenaline in a BGE of 20 mM citric acid/NaOH, pH 3.2. An intensity of 2.7 kV/cm was attained in the separation part of the capillary at a separation voltage of 30 kV, which is 2.9 times more than maximum intensity value attainable in a capillary with the same length with uniform id. At these high electric field intensities, the migration times of the tested neurotransmitters had values of 12.3-13.3 s and the attained separation efficiency was between 2350 and 2760 plates/s. It is thus demonstrated that an effective separation instrument - a coupled capillary - can be used for very rapid separation in combination with standard, commercially available instrumentation.
Keywords: Citric Acid; Time Factors; chemické modely; časové faktory; neurotransmiterové látky; Models, Chemical; hydroxid sodný; Electrophoresis, Capillary; Sodium Hydroxide; Neurotransmitter Agents; elektroforéza kapilární; katecholaminy; Catecholamines; kyselina citronová